Experimental investigation on the coolability of nuclear reactor debris beds using seawater. (March 2022) - Ahmed, Zayed; Jordan, Chance; Jain, Prashant; Robb, Kevin; Bindra, Hitesh; Eckels, Steven J.
Highlights: Coolability of nuclear reactor debris beds is studied experimentally. Distributed temperature sensing is used to depict local dryout heat flux. Influence of seawater impurities on the dryout flux is examined. Abstract: During the Fukushima nuclear reactor accident, seawater was injected into the reactor core to cool the decay heat from the heat generating porous debris bed. However, the impact of dissolved salts in water on the coolability of a debris bed is not well understood. This paper is one of the first works to investigate the cooling mechanisms for debris bed using seawater. An experimental system was built where the packed bed test section was volumetrically heated via a high frequency induction heater. The temperature along the axis of the test section was measured using a high resolution temperature sensor based on Optical Frequency Domain Reflectometry. Experimental results show that the dryout heat flux increases with an increase in concentration, with pure water having a dryout volumetric heat flux of 1.8 MW/m 3 and salt water of concentration 7% having a dryout volumetric heat flux of 2.8 MW/m 3 . However, this enhanced coolability using salt water is short term, as the crystallization fouling mechanism becomes significant over time and leads to gradual temperature excursion in the bed. The fouling mechanism eventually leads to a cross section of the debris bed to plug with the deposited salts, and this leads to a pressure build up in the lower regions of the debris bed.